Od podziału postsolidarnościowego do polaryzacji. (Krótkie) studium relacji między Prawem i Sprawiedliwością a Platformą Obywatelską i ich wyborcami - Zagała, Zbigniew (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2023)
The ongoing dispute between the parties – Law and Justice and Civic Platform – bears the hallmarks of total polarization. This polarization is present in almost all spheres of social life. In all of them, there is a constant confrontation between the parties involving their leaders and members, voters, and the vast majority of members of society. This process started in 2005 after a failed attempt to form a coalition government (POPiS) that was announced during the election campaign. The essential dynamics of this process were driven by affective factors and, to a much lesser extent, by ideological ones. The article attempts to look at the polarization in contemporary Polish society and answer some of the questions related to this problem: How was the polarization initiated? How did it develop? What are its specifics? The observations and the conclusions are formulated based on the results of quantitative surveys carried out by a variety of institutions, especially the Public Opinion Research Center.